An investigation into linguistic expressions of interpersonal meaning and their translational equivalents in the tale of kieu and its english version - Nguyễn,Thị Ly Thảo (ĐHĐN., 2015)
The purpose of the study is to find out linguistic expressions of interpersonal meanings and their translational equivalents in The Tale of Kieu and its English version. The model adopted for this paper is Halliday‟s systemic functional linguistics (SFL), mainly, interpersonal function. The Tale of Kieu is a masterpiece that is wellknown among not only Vietnamese people but people around the world as well. It is a potential source of interpersonal meanings with their own features. This paper explores the interpersonal meaning of mood, modality, vocatives and interpersonal grammatical metaphors. The paper draws a conclusion that the Hallidayan approach can be applied to some extent to the teaching and learning English for Vietnamese learners. In both English and Vietnamese, the interpersonal meaning is realized in the mood system, modality, vocative expressions and interpersonal grammatical metaphors.